2012
DOI: 10.1097/mao.0b013e3182423175
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Algorithm for Intraoperative Monitoring During Cochlear Implantation

Abstract: Immediate intraoperative determination of device functionality and optimal electrode placement is advantageous. Of the modalities tested, including electrode impedance, tNRT, and plain radiograph, only the radiographic results impacted intraoperative surgical decision making and led to the use of the backup device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 27 publications
5
71
0
3
Order By: Relevance
“…This is a technique that clinicians should utilize in the presence of intraoperative or postoperative electrode abnormalities, particularly OCs [13]. Our results are in agreement with that reported by Cosetti et al [10] who found that air bubbles are the commonest cause of abnormal intraoperative impedance.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This is a technique that clinicians should utilize in the presence of intraoperative or postoperative electrode abnormalities, particularly OCs [13]. Our results are in agreement with that reported by Cosetti et al [10] who found that air bubbles are the commonest cause of abnormal intraoperative impedance.…”
Section: Discussionsupporting
confidence: 95%
“…multielectrode array misplacement can be corrected intraoperatively once the surgeon is aware of it while the patient is still under anesthesia [10].…”
mentioning
confidence: 99%
“…The findings of our study argue for routine radiographic position checks because intraoperative findings only have a limited predictive value. This conclusion is in accordance to surgeons who rank radiographic position checks as so important that they perform intraoperative position checks, for example, (9,10), which have the added advantage that instant corrections of electrode position can be performed.…”
Section: Discussionsupporting
confidence: 86%
“…A digital copy of the film is saved in the patient record. A study of 288 surgeries using Nucleus CIs done at our institution (Cosetti et al, 2012) showed five instances of tip rollover or extracochlear electrode placement, which were all corrected after being detected in the intraoperative X-ray.…”
Section: Methodsmentioning
confidence: 99%